Peran Dinas Koperasi dan UKM Dalam Meningkatkan UMKM di Rantau Prapat Kabupaten Labuhanbatu - Junita Wulandari Dalimunthe; Muhammad Arif (VISA: Journal of Vision and Ideas, 2022)
One of the roles of the Rantau Prapat City Cooperatives and SMEs Service is to empower MSMEs in Rantau Prapat City, which has been stated in the Rantau Prapat City Cooperatives and SMEs Service. the realization of SMEs as an economic force that can improve the welfare of the community. Micro-enterprises in practice can help many people, considering that most Indonesian citizens belong to the lower-middle class category. From economic practice, they are classified as business actors in micro-economics. If the government's policies are in favor of groups of micro- economic actors, then it is possible that the policy will help many members of the community. That is, some Indonesian people will be lifted from poverty as a disease that afflicts the wider community. The purpose of this study is to identify and describe the implementation of SME empowerment as well as the supporting and inhibiting factors. This study uses descriptive research with a qualitative approach. The focus of this research problem is (1) the implementation of SME empowerment (2) supporting factors and inhibiting factors. and inhibitors. The advice given is that the Department of Cooperatives and SMEs in Labuhan Batu City collects data on all SMEs. Keywords ; Role, UMKM, Labuhan Batu, Rantau Prapat, Indonesia